2014
DOI: 10.3390/ijerph110808193
|View full text |Cite
|
Sign up to set email alerts
|

E-Health Interventions for Suicide Prevention

Abstract: Many people at risk of suicide do not seek help before an attempt, and do not remain connected to health services following an attempt. E-health interventions are now being considered as a means to identify at-risk individuals, offer self-help through web interventions or to deliver proactive interventions in response to individuals’ posts on social media. In this article, we examine research studies which focus on these three aspects of suicide and the internet: the use of online screening for suicide, the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
99
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(102 citation statements)
references
References 42 publications
(50 reference statements)
2
99
0
1
Order By: Relevance
“…Specifically, web-based tools have important benefits over in-person treatment that correspond to the identified barriers to mental health care for physicians including: 1) enhanced confidentiality; 2) low cost; 3) easy accessibility; 4) flexibility in timing of access; and 5) self-management tools 5, 14-16 . To date, five randomized controlled trials have demonstrated a reduction in suicidal thoughts among adult individuals in the general population and primary care settings using web-based cognitive behavioral therapy programs 17 . Recent work has also demonstrated the efficacy of web-based preventative interventions for populations at high risk for mental health problems 18,19-20 , but this preventative approach has not yet been tested in training physicians.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, web-based tools have important benefits over in-person treatment that correspond to the identified barriers to mental health care for physicians including: 1) enhanced confidentiality; 2) low cost; 3) easy accessibility; 4) flexibility in timing of access; and 5) self-management tools 5, 14-16 . To date, five randomized controlled trials have demonstrated a reduction in suicidal thoughts among adult individuals in the general population and primary care settings using web-based cognitive behavioral therapy programs 17 . Recent work has also demonstrated the efficacy of web-based preventative interventions for populations at high risk for mental health problems 18,19-20 , but this preventative approach has not yet been tested in training physicians.…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing interest in the use of digital technologies to deliver behavioral and mental health interventions, owing to their low delivery costs and tailorability (11,19,57). Strategies such as fractional factorial designs should be more widely considered for such studies because the technology can easily facilitate control over the combination of intervention components delivered.…”
Section: Discussionmentioning
confidence: 99%
“…Internet can be used to self-screening as well as to report to the psychiatric services providers that ultimately reduces the suicidality and further attempts. 39 Both guided & unguided web applications can be used to intervene the suicide. 39,40 Another approach to indentify the risky people by assessing the social media contents such as status updates, posts, comments those are indicative of mental disorders or suicidal ideation.…”
Section: E-health Interventionsmentioning
confidence: 99%
“…39,40 Another approach to indentify the risky people by assessing the social media contents such as status updates, posts, comments those are indicative of mental disorders or suicidal ideation. 39,40 Web-based video and podcasting, outreach communications via e-mail, smartphones applications, computer and web-based gaming, text analysis and so forth strategy can be implemented to identify the risky person and to direct them to the services providers. 40 …”
Section: E-health Interventionsmentioning
confidence: 99%